DAMPAK PELAKSANAAN STOCK SPLIT PADA HARGA SAHAM PERUSAHAAN - Natal Rino Samuel (2022)
Shares are proof of ownership or deed in the capital of a limited liability company that can be traded both inside and outside the capital market, which is a claim on the company's income and wealth; has the right to dividends in accordance with the paid-up capital specified in the company's articles of association. In the sale and purchase of shares there is a corporate action, namely every action or action of a company that affects changes in the market for both investors and the company. One of the corporate actions taken by the company is a stock split, which is an action to split the number of shares with the aim of making prices more affordable and market transactions more liquid. The purpose of this final project is to determine the changes between stock prices before and after the stock split and to determine the impact of the stock split implementation. When the issuer does a stock split, what happens is that the price of a stock becomes cheaper so that many retail investors are interested to buy. This study aims to determine the price changes of the issuer before the stock split and the price at the end of the year closing, as well as knowing the impact of the stock split.